Learning Arduino as a Simple River Water Level Detection System Based on Ultrasonic Sensors - Bertha Anggita Purwandani; Dimitra Ega Lianny; Melani Fitri Anggraeni; Putri Fauziah; Nugroho Adi Pramono; Rahmat Hartawan (Universitas Negeri Malang, 2021)
Current technological advancements are rapidly and impact daily life. Developing technology can be applied in many programs, one of which is as a tool for education. As shown in this study, technology as a mode of learning can be implemented in daily life. This study examined Arduino programming to create a river water level detection system using an ultrasonic sensor. This research is expected to be used as a learning tool for using Arduino as a microcontroller and can be applied in daily life. Additionally, by developing this river water level detection system, it will be possible to mitigate flood disasters.